Keragaan Unit Penangkapan Ikan di Pangkalan Pendaratan Ikan (PPI) Lhok Bengkuang Kecamatan Tapaktuan Kabupaten Aceh Selatan - Andriana, Mutia Rifka; Hafinuddin, Hafinuddin; Zuraidah, Syarifah; Fuadi, Afdhal (JURNAL PERIKANAN TROPIS, 2023)
South Aceh currently has 5 fish landing base points (PPI), namely PPI Lhok Bengkuang, PPI Labuhan Haji, PPI Sawang Ba'u, PPI Keude Mekek and PPI Keude Bakongan. There are three types of fishing fleets in South Aceh in 2019, namely motorboats, motorboats, and non-motorized boats. The fishing gear used by South Aceh fishermen is fishing rods, gill nets, shrimp nets, ring trawls, payang, rawai, tonda, beach trawls and bagan. The purpose of this study is to find out the types of fishing gear and fish catches in PPI Lhok Bengkuang. Penelitian ini dilaksanakan pada bulan Oktober sampai November 2022, data yang diambil yaitu data primer dan data sekunder, data primer berupa data koesioner sebanyak 44 responden. The method of selecting respondents was carried out by the purposive sampling method for fishermen at PPI Lhok Bengkuang and secondary data was obtained from related agencies. This research method uses descriptive analysis, the data analysis process is in accordance with the instructions in the Decree of the Minister of Fisheries and Fisheries Regulation number 6 of 2010 concerning fishing equipment in the national standard WPPRI. The results of the study showed that there were 3 main fishing gear at PPI Lhok Bengkuang that were environmentally friendly, namely stretch fishing rods, bottom fishing gear and ring trawls, then there was 1 type of fishing gear that was prohibited, namely fishing gear that used a compressor. The type of fishing gear is included in PermenKP No. 6 of 2010 at PPI Lhok Bengkuang.